Islam Nusantara Dalam Perspektif Pemikiran Liberal Abdurrahman Wahid: Islam Nusantara from the Perspective of Abdurrahman Wahid's Liberal Thought - Ubaidillah Ubaidillah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
Indonesia’s ethnically and religiously plural society is highly prone to conflict, particularly when issues of ethnicity, religion, race, and intergroup relations are disturbed. Abdurrahman Wahid (Gus Dur) developed liberal thought emphasizing democracy, pluralism, and the indigenization of Islam as the foundation of national life. This study aims to examine Gus Dur’s liberal thought on Islam Nusantara within the context of post-New Order political struggles. The method used is library research with a qualitative-descriptive approach, analyzing Gus Dur’s works and related literature. The results show that Gus Dur rejected the structural formalization of Islam, instead prioritizing the moral, ethical, and spiritual substance of Islam in state life. He believed Pancasila is final because none of its values contradict Islamic principles. In conclusion, Gus Dur’s Islam Nusantara prioritizes openness, tolerance, and respect for minorities. The recommendation is that interreligious and social-humanitarian dialogue must be continuously enhanced to maintain national harmony. Masyarakat Indonesia yang plural secara etnis dan agama sangat rentan terhadap konflik, terutama jika isu suku, agama, ras, dan antargolongan terganggu. Abdurrahman Wahid (Gus Dur) mengembangkan pemikiran liberal yang menekankan demokrasi, pluralisme, dan pribumisasi Islam sebagai landasan kehidupan berbangsa. Penelitian ini bertujuan mengkaji pemikiran liberal Gus Dur tentang Islam Nusantara dalam konteks pergulatan politik pasca-Orde Baru. Metode yang digunakan adalah studi kepustakaan dengan pendekatan kualitatif-deskriptif, menganalisis karya-karya Gus Dur dan literatur terkait. Hasil penelitian menunjukkan bahwa Gus Dur menolak formalisasi Islam secara struktural, sebaliknya mengedepankan substansi moral, etika, dan spiritual Islam dalam kehidupan bernegara. Ia meyakini Pancasila final karena tidak bertentangan dengan prinsip dasar Islam. Kesimpulannya, Islam Nusantara versi Gus Dur mengedepankan keterbukaan, toleransi, dan penghormatan terhadap minoritas. Rekomendasinya, dialog antaragama dan sosial-kemanusiaan perlu terus ditingkatkan untuk menjaga kerukunan nasional.